Editor's Foreword (Georgica, 1978)
The Journal Georgica (fields: Philosophy, Linguistics, History, Literary and Art Studies) was founded on June 9, 1977 at the formal founding ceremony, which took place in the Senate Hall of Friedrich Schiller University... The Rectors of Tbilisi State University and the University of Jena act as publishers. The publication is managed and its content determined by an editorial board and furthermore, the heads of the publishing departments of both universities.